Which Is the Optimum Antigen Concentration for the Venereal Disease Research Laboratory Test of Cerebrospinal Fluid for Neurosyphilis Diagnosis: 10 or 17 μL? - Xiao, Yao; Li, Wei; Li, Qiu-Ling; Xu, Qiu-Yan; Yang, Yang; Yang, Tian-Ci; Liu, Li-Li; Gu, Wei-Ming (Frontiers in Medicine, 2022)
The venereal disease research laboratory (VDRL) antigen is tested only with serum in manufacturing, without procedures for cerebrospinal fluid (CSF) testing. This study compared the CSF-VDRL test with 10 μL of antigen (CSF-VDRL-10) according to the American Public Health Association, to the CSF-VDRL test with 17 μL of antigen (CSF-VDRL-17) according to the VDRL serum procedure. A total of 121 neurosyphilis patients and 86 syphilis/non-neurosyphilis patients were included. The sensitivities of the CSF-VDRL-10 and CSF-VDRL-17 tests were comparable for neurosyphilis diagnosis. The positive rate of the CSF-VDRL-17 test was higher than that of the CSF-VDRL-10 test. There were 78.3% of the quantitative CSF-VDRL-17 results consistent with the CSF-VDRL-10 test, 18.4% with one-titer higher results than those from the CSF-VDRL-10 test, and 3.4% with positive CSF-VDRL-17 but negative CSF-VDRL-10 results. The CSF-VDRL test with 17 μL of antigen was more sensitive and it is worth performing longitudinal studies to understand its practical implications.